Persistent Pain After Decompression: Unmasking the Role of Facet Joint Pathology - Ahmad Ramdan; Greesea Dinamaria Whitiana; Felix Norman Christian Dachi (Newinera Publisher, 2026)
Lumbar facet joint cysts are an uncommon but important cause of radiculopathy, often associated with degenerative changes and segmental instability of the facet joint. Although endoscopic resection effectively relieves nerve root compression, persistent axial low back pain remains a frequent postoperative problem, likely because the underlying facet pathology is not fully addressed. This study assessed long-term outcomes after endoscopic cyst resection, with emphasis on persistent axial pain. A retrospective cohort study was conducted at a tertiary care center involving patients who underwent endoscopic laminotomy and resection of MRI-confirmed lumbar facet joint cysts between January 2022 and December 2025. Only patients with at least 24 months of follow-up were included. Demographic, clinical, surgical, imaging, and outcome data were reviewed. The primary endpoint was persistent axial low back pain at 24 months measured by Visual Analog Scale (VAS) and Oswestry Disability Index (ODI). Secondary outcomes included facet degeneration and cyst recurrence on imaging. Twenty-seven patients met inclusion criteria. Radicular symptoms improved in 90.5% of cases. VAS and ODI scores improved significantly at 24 months (p < 0.01). However, 59.2% (16 patients) continued to report axial low back pain. Follow-up MRI often showed progressive facet degeneration and residual or recurrent cysts in symptomatic patients. Conservative treatment gave limited benefit, and these patients later required percutaneous pedicle screw fixation. Endoscopic cyst resection reliably improves radicular symptoms, but persistent axial pain remains common when facet pathology is untreated. Adjunctive procedures such as facet denervation or segmental stabilization may improve long-term outcomes. Prospective studies are needed to define the role of these additional techniques.